Functionalized Imidazolium Bis(trifluoromethylsulfonyl)imide Ionic Liquids for Gas Sensors: Solubility of H2, O2 and SO2 - Doblinger, Simon; Silvester-Dean, Debbie; Costa Gomes, M. (2021)
Gas solubilities of non-polar (hydrogen and oxygen) and polar (sulphur dioxide) gases in a set of functionalized alkyl imidazolium ionic liquids with the bis(trifluoromethylsulfonyl)imide ([NTFf2]−) anion are reported between 303 and 333 K at 1 bar. The alkyl side-chains in the imidazolium cations include different functional groups, such as –OH, –CN and benzyl; their effects on gas solubilities were studied. The solubility decreases with temperature for all gases, as expected for an exothermic dissolution. Sulphur dioxide is by far the most soluble gas, with mole fractions between 0.29 and 0.41 in the ionic liquids at 313 K and 1 bar, approximately 2–3 orders of magnitude higher than the two other gases studied. Oxygen is generally more soluble in the ionic liquids than hydrogen with mole fractions ranging from 9 × 10−4 to 21 × 10−4 and 5 × 10−4 to 15 × 10−4 at 313 K and 1 bar for oxygen and hydrogen, respectively. In the case of hydrogen, the solubility increases when the molar volume of the ionic liquid increases, whereas for oxygen, the presence of polar groups in the cation causes a reduction in the solubility. None of the three gases is chemically absorbed in the ionic liquids.